Composición de aves acuáticas y ribereñas migratorias en época de vaciante en el río Ucayali, Loreto - Perú - Coblentz Reyna, Benjamin Alexis (2022)
Since august to October 2018, we studied acuatics and riveredge birds in season not flooded in the Ucayali river by census in boat (modified by Acosta). We report a especific richness the 21 species of birds, between acuatics and riveredge, in the Pelecaniformes, Accipitriformes, Charadriiformes and Passeriformes Order, where the Charadriiformes order report 4 families predominating the Scolopacidae and Charadriidae families, following of the Passeriformes order with 3 families, Accipitriformes order with 2 and the Pelecaniformes order with 1 family. To taxonomic level the species, the Charadriiformes order with 10 species, Passeriformes order with 6, Accipitriformes order with 4 and Pelecaniformes order with 1, and the density of the migratory acuatics and riveredge birds in season not flooded in the Ucayali river was low for all the species registered. Us concluded that the Ucayali river report a low diversity and abundance.